Saving-enhanced performance: saving items after study boosts performance in subsequent cognitively demanding tasks. Issue 10 (26th November 2019) - Runge, Yannick; Frings, Christian; Tempel, Tobias
ABSTRACT: By saving and storing information, we use digital devices as our external memory stores, being able to offload and temporarily forget saved contents. Storm and Stone [2015. Saving-enhanced memory: The benefits of saving on the learning and remembering of new information. Psychological Science, 26 (2), 182–188] showed that such memory offloading can be beneficial for subsequent memory performance. Saving already encoded items enhanced recall of items encoded after saving. In the present study, we did not only replicate saving-enhanced memory but found saving-enhanced performance for unrelated cognitively demanding tasks. Participants solved more modular arithmetic problems when they were able to offload a previously studied word list, compared to trials without the possibility to offload. Thus, saving of recently encoded items entailed a general benefit on subsequent cognitive performance, beyond encoding and retrieving word lists. We assume that offloading frees participants from the need to maintain offloaded items. Gained resources can then be used for subsequent tasks with high cognitive demands. In a nutshell, memory offloading can help to reduce the amount of information that has to be processed at a given time, efficiently delegating our limited cognitive resources to the most relevant tasks at hand while currently irrelevant information are safely stored outside our own memory.